Woman as Victim of Manipulation: The Example of Fyodor Dostoyevsky’s Netochka Nezvanova - Lekeš, Patrik (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article analyzes the relationship between daughter and stepfather in Fyodor Dostoyevsky’s Netochka Nezvanova (1849), perceiving the presence in it of symptoms of three socio-psychological phenomena – the Electra Complex, codependency, and gaslighting. Dostoevsky sees man as a “mystery” and explores the “bottom of the human soul”. Using the material of Dostoevsky’s novel, the article demonstrates the productivity of the psychological approach to Dostoevsky’s work. It seeks to place this classical text of Russian literature within the paradigms of modern psychology and to show the author’s mastery and insight in describing the above-mentioned socio-psychological phenomena already in the 19th century, although they were determined by modern science only at the turn of the 20th–21st centuries. This analysis also allows us to think about the main character as a victim of manipulation. Symptoms of each of these social-psychological phenomena are present in the behaviour of Netochka. All these forms of manipulation are the result of her stepfather’s addiction. However, it remains moot to what extent they are present in the psyche of the protagonist.